Kissing Christians : ritual and community in the late ancient church - Penn, Michael Philip (Divinations., 2005)
"Kissing Christians presents the first comprehensive study of the ritual kiss and how controversies surrounding it became part of larger debates regarding the internal structure of Christian communities and their relations with outsiders. Penn traces how Christian writers exalted those who kissed only fellow Christians, proclaimed that Jews did not have a kiss, prohibited exchanging the kiss with potential heretics, privileged the confessor's kiss, prohibited Christian men and women from kissing each other, and forbade laity from kissing clergy." "Kissing Christians also investigates connections between kissing and group cohesion, kissing practices and purity concerns, and how Christian leaders used the motif of the kiss of Judas to examine theological notions of loyalty, unity, forgiveness, hierarchy, and subversion." "Exploring connections between bodies, power, and performance, Kissing Christians bridges the gap between cultural and liturgical approaches to antiquity. It breaks significant new ground in its application of literary and sociological theory to liturgical history and will have a profound impact on these fields."--Jacket